2011
DOI: 10.1146/annurev-phyto-072910-095323
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Targets of Phytoplasma Effectors: From Plant Development to Defense Against Insects

Abstract: Phytoplasma research begins to bloom (75). Indeed, this review shows that substantial progress has been made with the identification of phytoplasma effectors that alter flower development, induce witches' broom, affect leaf shape, and modify plant-insect interactions. Phytoplasmas have a unique life cycle among pathogens, as they invade organisms of two distinct kingdoms, namely plants (Plantae) and insects (Animalia), and replicate intracellularly in both. Phytoplasmas release effectors into host cells of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
218
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 242 publications
(228 citation statements)
references
References 91 publications
1
218
0
9
Order By: Relevance
“…Owing to the significant reduction in the genome of phytoplasmas, they cannot be cultured in vitro and are restricted to phloem sieve cells with a rich growth environment (Oshima et al, 2004;Bai et al, 2006). Although phytoplasmas depend on their plant host for survival, they are able to manipulate the plant's physiology through their secreted effectors (Sugio et al, 2011a).…”
mentioning
confidence: 99%
“…Owing to the significant reduction in the genome of phytoplasmas, they cannot be cultured in vitro and are restricted to phloem sieve cells with a rich growth environment (Oshima et al, 2004;Bai et al, 2006). Although phytoplasmas depend on their plant host for survival, they are able to manipulate the plant's physiology through their secreted effectors (Sugio et al, 2011a).…”
mentioning
confidence: 99%
“…Aster Yellows phytoplasma strain Witches' Broom (AY-WB; Candidatus Phytoplasma asteris) is vectored by the polyphagous aster leafhopper Macrosteles quadrilineatus, which readily transmits this pathogen to a wide range of plants, including members of the Solanaceae and Brassicaceae families (Sugio et al, 2011). Phytoplasmas such as AY-WB induce a variety of symptoms in plants that are indicative of an abnormal development of host tissues, including the formation of witches' broom (a dense mass of shoots originating from a single point), phyllody (conversion of floral organs into leaves), virescence (green pigmentation of tissues such as flower petals), and bolting (growth of elongated stalks).…”
mentioning
confidence: 99%
“…Phytoplasmas such as AY-WB induce a variety of symptoms in plants that are indicative of an abnormal development of host tissues, including the formation of witches' broom (a dense mass of shoots originating from a single point), phyllody (conversion of floral organs into leaves), virescence (green pigmentation of tissues such as flower petals), and bolting (growth of elongated stalks). We hypothesized that phytoplasmas secrete virulence pro-teins (effectors) to induce such alterations in phenotype of host plants Bai et al, 2009;Sugio et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 The identification of phytoplasma-secreted proteins has revealed that phytoplasma effectors are virulence factors responsible for inducing morphological changes in infected plants. 4,5 For example, SAP11 secreted by the Aster Yellows phytoplasma strain Witches' Broom (AY-WB) and TENGU secreted by the Onion Yellows phytoplasma strain M (OY-M) induce the proliferation of branches similar to the witches' broom symptom.…”
mentioning
confidence: 99%